Professional mobility and the reshaping of the identity of Algerian working women Field study on a sample of working women in The City of bordj bou arreridj - lacheheb, nassima (Journal of Social Sciences and Humanities, 2020)
This study aimed at identifying the contribution of professional mobility in reshaping the identity of Algerian working women and social integration, and was conducted on a sample of working women, which singled out the category of tires in the public administration sector in the city of Bordj Bou arreridj, which numbered 110 individuals, and has been used Or the descriptive analytical approach to describe the phenomenon as it is in fact as it is as it is, and through the results it became clear that the higher the woman working in the hierarchy, the more this leads to a change in her lifestyle and relationships with the individuals around her, especially within the family environment, as her relationship with the family has diminished, And moved towards the creation of other alternative social bonds, and as the dynamics of the career allows it to provide the opportunity to prove oneself and the ability to achieve material and moral independence, the hierarchy of jobs is also one of the factors that contribute to changing the social status of women, the professional status has a role to play in making it As it may be noted that the rising movement has allowed the change of society's perception towards it as a result of the shift in the cultural value pattern in Algerian society, and to break into positions of responsibility have a relative impact on the employment of working women within their families, they are always in a struggle to try to The refore, the professional mobility, especially the rising movement, has changed its status and social status, and has allowed it to prove itself and change the way society looks at it and thus reshape its identity, considering that identity is not a constant thing. It is an ongoing process and is linked to the course of the individual's cv or career path